Waste-derived glass as a precursor for inorganic polymers: From foams to photocatalytic destructors for dye removal. Issue 19 (1st October 2022) - Mehta, Akansha; Colusso, Elena; Kraxner, Jozef; Galusek, Dusan; Bernardo, Enrico
Abstract: Synthetic alumino-silicate glasses may yield inorganic polymers, through activation with alkali hydroxide solutions. In this framework, we formulated a glass prepared by the melting of red mud from bauxite refinement, combined with coal combustion fly ash, discarded pharmaceutical glass and a minor addition of sodium carbonate. The activation with 6 M NaOH aqueous solution allowed for the manufacturing of highly porous foams, by gas generation at the early stages of gelation. These foams featured an extensive formation of zeolite at cell walls which, combined with the presence of magnetite formed upon cooling of the melt, favoured the application of the foams as sorbents for dye removal from contaminated water. The powders prepared by crushing the highly porous foams showed an excellent water purification ability documented by efficient removal of methylene blue used as a model contaminant. The specific iron oxide polymorph facilitated both magnetic recovery of dispersed powders and photocatalytic destruction of the dye under UV irradiation.